Functionalization of cotton fabric with chitosan microspheres containing triclosan - Magalhaes, L. G.; Lima, C. S. A. de; Costa, S. M. da; Santos, A. C. S. [UNESP]; Costa, S. A. da; Montagna, G.; Carvalho, C. (Crc Press-taylor & Francis Group, 2019)
Medical textiles are structures designed for use within the medical field and can be classified into surgical textiles, extra body systems and hygiene and health products. Chitosan is a natural polymer with interesting properties such as bactericidal activity, biocompatibility and non-toxicity. In this work, an antibacterial finish for hospital fabrics was developed from the synthesis of chitosan microspheres with the incorporation of the triclosan drug. The finish was impregnated in 100% cotton fabric with twill structure. The fabric was characterized by mass per unit area, yarns linear density and yarns density determination tests. Optical microscopy analyzes were performed and showed that the microspheres were impregnated between the fibers of the fabric. The material, therefore, presented potential for application as a finish for fabrics used in the medical area.